Bio-aggregates based building materials : state-of-the-art report of the RILEM Technical Committee 236-BBM - Amziane, Sofiane; Collet, Florence (Springer, 2017)
The work of the RILEM Technical Committee (TC -236 BBM) was dedicated to the study of construction materials made from plant particles. It considered the question whether building materials containing as main raw material recyclable and easily available plant particles are renewable. This book includes a state-of-the-art report and an appendix. The state-of-the-art report relates to the description of vegetal aggregates. Then, hygrothermal properties, fire resistance, durability and finally the impact of the variability of the method of production of bio-based concrete are assessed. The appendix is a TC report which presents the experience of a working group. The goal was to define testing methods for the measurement of water absorption, bulk density, particle size distribution, and thermal conductivity of bio aggregates. The work is based on a first round robin test of the TC-BBM where the protocols in use by the different laboratories (labs) are compared.
Keywords: Plant fibers as building materials.; Aggregates (Building materials); Sustainable buildings -- Design and construction.; Recycled products.; elektronické knihy; electronic books